Peptides from animal and fishery byproducts: uplifting the functionality of fifth quarter - Verma, Akhilesh Kumar; Umaraw, Pramila; Kumar, Pavan; Mehta, Nitin; Sharma, Neelesh; Kumar, Devendra; Sazili, Awis Qurni; Lee, Sung Jin (John Wiley and Sons, 2025)
The meat and fish sectors are primary sources of animal protein for human consumption. However, they also generate large volumes of byproducts and organic waste annually, posing major challenges in terms of sustainable disposal. These byproducts have the potential to be repurposed into high-value, low-volume products, such as bioactive peptides or hydrolysates. Various methods used for the recovery of bioactive peptides from meat byproducts are enzymatic hydrolysis, microbial fermentation, ultrasonic-assisted, pulsed electric field, high hydrostatic pressure, microwave-assisted, and subcritical water processing. These bioactive peptides possess various functional properties, including antioxidant, antimicrobial, and antihypertensive effects. Incorporating them into food products could enhance both the functionality and quality of these products. In light of growing consumer demand for natural, eco-friendly ingredients, as well as sustainable practices in food production and packaging, the generation and use of bioactive peptides and hydrolysates offer a promising strategy. This approach not only mitigates environmental challenges but also fosters the sustainable growth of the meat and fishery industries, ensuring long-term ecological and economic viability. This review explores new opportunities and avenues for utilizing animal and marine byproducts in producing bioactive peptides and their potential applications in meat products and processing techniques, thereby supporting the sustainable growth of the meat and fishery industries.